Effects of Additional Administration of a Selective Inhibitor of Sodium Glucose co-transporter-2 Inhibitor on the Glycemic Control in Japanese Type 2 Diabetes Mellitus Patients Receiving Treatment with a Dipeptidyl Peptidase-4 Inhibitor - Kusunoki, Masataka; Sato, Daisuke; Sakazaki, Takahiko; Miyata, Tetsuro; Tsutsumi, Kazuhiko; Oshida, Yoshiharu (Drug Research, 2020)
We conducted this study to determine whether additional administration sodium-glucose co-transporter 2 (SGLT2) inhibitor might provide further improvement of glycemic control and also to explore any advantages in Japanese type 2 diabetes patients showing relatively good glycemic control under treatment dipeptidyl peptidase-4 (DPP-4) inhibitors. We divided the patients in two groups, MT group and CT group. The MT group were continued on the DPP-4 inhibitor treatment for 6-months, and CT group were additionally administered an SGLT2 inhibitor treatment for 6-months. The MT group showed a significant decrease of hemoglobin A1c (HbA1c), but a significant increase of body weight, body mass index and serum uric acid, compared to the baseline values, while the CT group showed a significant decrease of HbA1c, body weight, BMI, and serum uric acid, and also a significant increase of serum HDL-cholesterol and decrease of serum triglyceride levels. Furthermore, this group showed a significant decrease of serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT) and gamma-glutamyl transpeptidase (γ-GTP), which are markers of liver function. These results suggest that the combination therapy is useful, in particular, for the treatment of type 2 diabetes mellitus patients with hyperlipidemia and liver dysfunction. Among the SGLT2 inhibitors added to the DPP-4 inhibitor treatment, the decreases of serum levels of AST, ALT and γ-GTP were particularly significant in the group receiving luseogliflozin, suggesting that the combination of a DPP-4 inhibitor with luseogliflozin is particularly effective for the treatment of type 2 diabetes mellitus patients with liver dysfunction.
Keywords: sodium-glucose co-transporter 2 inhibitor; dipeptidyl peptidase-4 inhibitor; type 2 diabetes, hemoglobin A1c